The effect of sociostructural and collaborative decision-making on diabetes self-management. - Isaac Rahimian Boogar; Mohammad Reza Mohajeri-Tehrani; Mohammad Ali Besharat; Seyavash Talepasand (Tehran University of Medical Sciences, 2013)
Diabetic self-management is important for controlling the diabetes complications and promoting health-related quality of life in these patients. The objective of this study was to examine a hypothetical model regarding influences of sociostructural determinants, collaborative decision-making and patient's beliefs system on diabetes self-management.In a cross-sectional descriptive study from Dec 2010 to Mar 2010, 500 patients of Iranian adult patients with type II diabetes attended the outpatient diabetic clinics of the Shariati Hospital in Tehran were selected by convenience sampling. Data were collected by The Demographical Information, Social- Economical Status and Diabetic History Questionnaire and eleven self-reported scales of this research. Structural equation modeling (SEM) with LIZREL software applied for data analysis.The modified model had a desirable fitness to the observed data. Patient's beliefs system directly influenced the diabetes self-management. Sociostructural determinants influenced diabetes self-management indirectly via collaborative decision-making and Patient's beliefs system. In addition, collaborative decision-making significantly influenced patient's beliefs system that thereby impacted diabetes self-management.Sociostructural determinants, collaborative decision-making and patient's beliefs system are integrated and cooperatively affect on diabetes self-management. Comprehensive intervention schedules required to improve these agents for encouragement the type II diabetes self-management.